Reconfigurable Diodes Based on Vertical WSe2 Transistors with van der Waals Bonded Contacts. Issue 18 (22nd March 2018) - Avsar, Ahmet; Marinov, Kolyo; Marin, Enrique Gonzalez; Iannaccone, Giuseppe; Watanabe, Kenji; Taniguchi, Takashi; Fiori, Gianluca; Kis, Andras
Abstract: New device concepts can increase the functionality of scaled electronic devices, with reconfigurable diodes allowing the design of more compact logic gates being one of the examples. In recent years, there has been significant interest in creating reconfigurable diodes based on ultrathin transition metal dichalcogenide crystals due to their unique combination of gate‐tunable charge carriers, high mobility, and sizeable band gap. Thanks to their large surface areas, these devices are constructed under planar geometry and the device characteristics are controlled by electrostatic gating through rather complex two independent local gates or ionic‐liquid gating. In this work, similar reconfigurable diode action is demonstrated in a WSe2 transistor by only utilizing van der Waals bonded graphene and Co/h‐BN contacts. Toward this, first the charge injection efficiencies into WSe2 by graphene and Co/h‐BN contacts are characterized. While Co/h‐BN contact results in nearly Schottky‐barrier‐free charge injection, graphene/WSe2 interface has an average barrier height of ≈80 meV. By taking the advantage of the electrostatic transparency of graphene and the different work‐function values of graphene and Co/h‐BN, vertical devices are constructed where different gate‐tunable diode actions are demonstrated. This architecture reveals the opportunities for exploring new device concepts. Abstract : Van der Waals bonded contacts are crucial to eliminate hybridization‐induced gap states formed at metal/2D semiconductor interfaces. WSe2 ‐based transistors employ such contacts (graphene and Co/h‐BN) to study their charge‐injection efficiencies. Benefiting from these asymmetric contacts, vertical devices demonstrate gate‐tunable diode action. These findings provide important insights for the development of next‐generation electronic applications based on 2D materials.